(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Gender is an important aspect of social and economic stratification. Regardless of one‘s socioeconomic class, there are systematic gender differences in material well-being, although the degree of inequality varies across countries and over time. The importance of gender equality, women‘s empowerment and the realization of women‘s rights in achieving development has been increasingly recognized in recent decades and it has also been realized in India. Women play an important role in every section of the society. A woman equally contributes to development of a nation as a man does. Thus, linking gender inequality and development is important for several reasons and this paper tries to highlight some of its reasons. This paper is an attempt to analyze the role of gender inequality in India, with specific focus on issues that might be expected to be the most critical for overall development of the country.This study using access to education and health as the indicators of gender inequality examines gender inequality and state level openness in the different states of India. Further, the study’s findings show that at the sub-national level in India higher per capita income is accompanied with lower gender inequality. However, in some high income states gender inequality is also very high.